Fostering Character Education in Elementary Schools: The Impact of Extracurricular Activities - Armadi, Ali; Jamilah, Jamilah; Wahdian, Agus; Astutik, Choli (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explores the role of effective extracurricular management in cultivating students who are creative, imaginative, and well-mannered. The primary aim of extracurricular activities is to complement the formal educational experience by offering opportunities to apply theoretical knowledge and practical skills gained in the classroom. The objective of this research is to enhance character education in elementary school students through participation in extracurricular activities. Utilizing a qualitative approach, the study seeks to present a comprehensive overview of the current situation and to provide an in-depth description of the factors at play, offering the reader highly accurate insights. The research is conducted at SDI Lukmanul Hakim Sumenep, a school consistently recognized among the top in the region since 2013 by the Sumenep Regency administration. Data sources include key informants such as the school principal, deputy head of curriculum, teachers, and students. Findings suggest that extracurricular activities contribute significantly to the improvement of character education, instilling values such as religious observance, honesty, tolerance, discipline, and responsibility. These outcomes are achieved through regular activities like teacher and student picket duty and flag ceremonies, as well as spontaneous initiatives such as advising, correcting behavior, and providing assistance with incidental tasks. Furthermore, examples and conditioning activities, including environmental cleanliness and character education taglines, reinforce these values. The positive impacts of these activities include the development of social skills and communication abilities, with the school environment playing a crucial role in shaping students' character.